2021
DOI: 10.1155/2021/6915329
|View full text |Cite
|
Sign up to set email alerts
|

piRNA-31115 Promotes Cell Proliferation and Invasion via PI3K/AKT Pathway in Clear Cell Renal Carcinoma

Abstract: PIWI-interacting RNAs (piRNAs) are small noncoding RNAs that play important roles in germline development and carcinogenesis. In this study, we used the deep sequencing of small RNA Transcriptome to explore the piRNA expression in six clear cell renal carcinoma (ccRCC) tissues and matched adjacent normal tissues and found that six piRNAs were upregulated and sixteen were downregulated in ccRCC tissues. Among them, piRNA-31115 (NCBI accession number: DQ571003) was the most upregulated piRNA in ccRCC tissues com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…However, none of the piRNA in our dataset mapped to LINE-1, suggesting another mechanism of action for these piRNA. This reasoning is supported by Du and colleagues who described the role of piR-31115 - also present in our dataset ( Supplementary File S2 )—in renal cell carcinoma progression by activation of epithelial-mesenchymal transition via the PI3K/AKT signaling, independently of L1 repression ( Du et al, 2021 ), as this piRNA also does not map to LINE-1.…”
Section: Discussionsupporting
confidence: 86%
“…However, none of the piRNA in our dataset mapped to LINE-1, suggesting another mechanism of action for these piRNA. This reasoning is supported by Du and colleagues who described the role of piR-31115 - also present in our dataset ( Supplementary File S2 )—in renal cell carcinoma progression by activation of epithelial-mesenchymal transition via the PI3K/AKT signaling, independently of L1 repression ( Du et al, 2021 ), as this piRNA also does not map to LINE-1.…”
Section: Discussionsupporting
confidence: 86%
“…DEGs among different m7G subtypes were enriched in cancer-related pathways, such as the positive regulation of cell adhesion, the positive regulation of vasculature development, cell molecule adhesion, the PI3K–Akt signaling pathway, and the AKT–STAT signaling pathway. PI3K–Akt signaling pathway activation can promote the metastasis and progression of RCC ( Du et al, 2021 ; Lin et al, 2021 ; Zhu et al, 2020 ). We divided the patients into three gene types in accordance with the three m7G subtypes and found significant differences in OS and PFS among the subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that piR-823 was significantly upregulated in the ALDH-positive breast CSCs, and piR-823 confers stem-like properties to breast cancer cells by activating the Wnt signaling pathway (Ding et al, 2021). In clear cell renal carcinoma cells, piR-31115 induces epithelialmesenchymal transition (EMT) via decreasing E-cadherin expression and increasing mesenchymal markers (Vimentin and Snail) (Du et al, 2021). These results suggest that the expression of certain piRNAs is required for the initiation and maintenance of CSCs, and the roles of piRNAs in gastrointestinal CSCs deserve further investigation.…”
Section: Therapeutic Approaches Using Piwi-interacting Rnasmentioning
confidence: 99%